AN INNOVATIVE APPROACH IN THE FIELD OF EDUCATION: SELF DIRECTED PROFESSIONAL DEVELOPMENT - Amna Saleem, Maria Shahid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In helping teachers to meet the demands of the modern world, self-directed professional development is essential. The process in which knowledge is created and guided by oneself is self-directed professional growth. The learner assesses his/her deficiencies in this process and strengthens his/her instructional methods and delivery paces. One of the most well-recognized current theories of education is self-directed learning. In imparting a Self-directed professional development attitude among students, teachers play a significant role. The role of teachers has shifted from teaching speakers to teaching facilitators. This article aims to analyze self-directed professional development its main features, essential strategy, advantages, challenges, and its implementation in the Pakistani scenario. This paper introduces and explores a more profound sense of self-directed professional development